Економічні та соціальні проблеми розвитку пенсійної системи України (на прикладі м. Києва) - Вернигора, Н.Ф. (Інститут демографії та соціальних досліджень НАН України, 2006)
Статья посвящена целесообразности реформирования пенсионной системы в Украине. В работе автор обратила внимание на основные преимущества трехуровневой системы пенсионного обеспечения, которая вводится в Украине. Автор делает акцент на действиях и мероприятиях, необходимых для создания дееспособной пенсионной системы нового образца и концентрирует внимание на основных задачах и направлениях деятельности Пенсионного фонда Украины. Clause is devoted to expediency of pension system reforming in Ukraine. The author has paid attention on the basic advantages of three-level system of a provision of pensions which is entered in Ukraine. The author does accent on actions necessary for creation of capable pension system of the new sample and concentrates attention on the primary goals and directions of activity of the Pension fund of Ukraine.